Synthesis of Substituted Quinolines Using the Friedlander Reaction Under Microwave Irradiation Techniques - Mehta, Prajakta; Jadhav, Sarika; Gadekar, Suchita; Sapkal, Suryakant; Gawai, Jaishree (Letters in Organic Chemistry, 2025)
3-(N-morpholino)propanesulfonic acid (MOPS), used as an organocatalyst supported on acidic alumina (Al2O3), has been effectively employed for the synthesis of substituted quinolines through the Friedlander reaction under microwave irradiation. The process involves the cyclocondensation of 2-aminoaryl ketones with carbonyl-functionalized active methylene groups. The catalytic efficacy of the MOPS/Al2O3 system proves compatible with this cyclocondensation reaction, offering several advantages including rapid activation of reactants, maintenance of a near-neutral pH, cost-effectiveness, and high yield.
Keywords: microwave assisted synthesis